An investigation into how EFL learners emotionally respond to teachers’ oral corrective feedback - Martínez, Juan de Dios (Colombian Applied Linguistics Journal, 2013)
This research study draws on research in SLA and language pedagogy and hopes to throw some light on the pedagogical effectiveness of the oral feedback process in L2 classrooms by focusing exclusively on the potential affective damage that teachers´ oral corrective feedback can cause among learners in classroom settings. The paper describes a study in which we investigated how EFL learners actually perceive or rather emotionally respond to the oral feedback process. This paper aims to investigate to what extent the way teachers provide oral corrective feedback is somehow associated with learners´ motivations and attitudes. For this purpose, a short questionnaire was designed and distributed among a sample of 208 EFL secondary school learners. The article first reviews the literature on the controversial role of corrective feedback in L2 classrooms. Next, the findings are reported and discussed. This research paper suggests that EFL learners emotionally respond to teachers´ oral corrective feedback in different ways. Additionally, it found evidence that anxiety can have a negative effect on the way learners benefit from the oral feedback process. Thus, the paper issues warnings about the potential affective damage oral corrective feedback can cause among learners in classroom situations.